Synthesis of control laws for magnetic levitation systems based on serial invariant manifolds - Chiem, Nguyen Xuan; Pham, Thuy Xuan (IAES International Journal of Robotics and Automation (IJRA), 2022)
In this paper, a nonlinear controller is designed for a magnetic levitation system (MLS) based on serial invariant manifolds. Synthesized controller based on the method of synergetic control theory (SCT) through invariant manifolds, asymptotically stable. In this method, the control law is synthesized to ensure the motion of the closed-loop control object from an arbitrary initial state into the vicinity of the desired invariant manifold. Thereby, the control system not only ensures the necessary control quality but also ensures the asymptotic stability of the entire system. The quality and efficiency of the control law are proven through simulation results and comparison with the sliding mode controller (SMC).